CONTACT SENSITIZATION TO METHACRYLIC MONOMERS AMONG DENTAL TECHNICIAN STUDENTS IN RELATION TO DURATION OF EDUCATIONAL EXPOSURE - Maya Lyapina; Todor Kundurjiev; Karolina Lyubomirova; Evgeny Stanev; Zaharina Savova (Peytchinski Publishing, 2019)
Purpose: Sensitization to methacrylic monomers is a significant problem in dental occupational exposures. The purpose of the present study was to evaluate the dynamics in contact sensitization incidence to methacrylic monomers during the educational course of dental technician students. Material and Methods: Skin patch testing with methyl methacrylate, triethylene glycol dimethacrylate, ethylene glycol dimethacrylate, 4-tolyldiethanolamine, N,N-Dimethyl-4-toluidine, 1,4-butanediol dimethacrylate, tetrahydrofurfuryl methacrylate, formaldehyde and glutaraldehyde was performed among 150 dental technician students (38 - 1st, 40 - 2nd and 38 - 3rd year of education); 34 students without educational exposure to metals served as controls.. Chi square test and Fisher Exact Test were used in data analysis (p < 0.05). Results: The incidence of sensitization to 4-tolyldiethanolamine in the group of dental technician students 2nd and 3rd year of education was significantly higher, if compared with those from the 1st year, as well as with the control group (P=0.042). The sensitization rate to 4-tolyldiethanolamine was the highest recorded among all methacrylic monomers tested for the whole tested population. The incidence of positive patch tests to formaldehyde was the highest recorded for all defined groups. Higher were sensitization rates among dental technician students 2nd year of education vs. no cases in the control group. Conclusions: Our data indicate high and increasing with the duration of educational exposure risk of contact sensitization to 4-tolyldiethanolamine among dental technician students, and this substance could be outlined as a sensitizer of prominent importance. No significant differences were established concerning the other tested methacrylic monomers. We accept the main role of consumer and environmental exposures for the manifestation of formaldehyde sensitization. Adequate preventive measures and information should be provided during the practical educational course of dental technician students. General population need to be well informed and the European Union regulations to be properly applied.